Las familias afines Un estudio doctrinal, jurisprudencial y comparado - Del Carmen-Iparraguirre, Denjiro (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2023)
The present work is not entirely a treatise. It is just a manual for the ease of understanding related families, assembled, composed, reconstituted or if we want social; as a new modality of constituting a family, therefore, it must also have a space within the civil code. The purpose is to carry out a doctrinal, jurisprudential and comparative analysis of this type of family and explain the most important changes that must be incorporated into the current civil code; Hoping it will be useful for all those who have a vocation for civil law.